Kulisseja - Kantrikustaa; Hämäläinen, Markku; Löytty, Sakari; Mäki-Lohiluoma, Jouko; Nuorva, Teppo; Ojalainen, Jyrki; Rantanen, Harri; Tiusanen, Petri; Vuorela, Auli; Wuolio, Seppo; Suikki Brass (Zero Records, 1982)
12 kappaletta.